Metal"“organic framework-based heterogeneous catalysts with tailored active sites for precise oxidative transformations - Hulushe, Siyabonga Theophillus (Rhodes University, Faculty of Science, Department of Chemistry)
Access restricted. Exected release in 2025.
Keywords: Uncatalogued